An Analytical and Predictive Approach of Statistical Technique for Air Pollutants - Kr. Yadav, Vijay; Goyal, P.; K. Yadav, V.; Singh, Akansha (International Journal of Engineering and Technology, 2018)
Urban air pollution has emerged as an acute problem in recent years because of its detrimental effects on health and living conditions. The prediction of concentration of air pollutants in urban areas has become a major focus area of air quality research today due to their health effects. In the present study statistical model based on neural network (NN) has been developed to predict the pollutants such as NOX, NO2 and particulate matters (PM2.5 and PM10 ) for Delhi city at different locations such as ITO (Income tax office), and DTU (Delhi technological university) . Error estimation is also done in this study.Â Â